2011
DOI: 10.1007/s10681-011-0412-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of wheat–rye 1BL.1RS translocation lines derived from different wheat and rye sources

Abstract: Many studies have been conducted to determine the relative effects of the 1BL.1RS translocation on various traits in wheat. The effects of different wheat (Triticum aestivum L.) genetic backgrounds and rye (Secale cereale L.) sources have been addressed as major factors for inconsistent agronomic performance and end-use-quality traits of 1BL.1RS translocation wheats. However, all these studies were accomplished by using 1BL.1RS translocations with impure wheat genetic bases and narrow rye origins. The objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 49 publications
0
66
0
4
Order By: Relevance
“…Помимо устойчивости к грибным патогенам, наличие хромосомы 1RS повышает адаптивность к условиям внешней среды, увеличивает биомассу и урожайность (Ehdaie et al, 2003;Kumlay et al, 2003;Kim et al, 2004;Ren et al, 2012). С использованием изогенных линий, содержащих сегменты 1RS хромосомы различной про тяженности, было показано, что генетические локусы, оказывающие положительный эффект на урожай, распо ложены в дистальном районе (Howell et al, 2014).…”
Section: влияние чужеродного генетического материала на проявление хоunclassified
See 1 more Smart Citation
“…Помимо устойчивости к грибным патогенам, наличие хромосомы 1RS повышает адаптивность к условиям внешней среды, увеличивает биомассу и урожайность (Ehdaie et al, 2003;Kumlay et al, 2003;Kim et al, 2004;Ren et al, 2012). С использованием изогенных линий, содержащих сегменты 1RS хромосомы различной про тяженности, было показано, что генетические локусы, оказывающие положительный эффект на урожай, распо ложены в дистальном районе (Howell et al, 2014).…”
Section: влияние чужеродного генетического материала на проявление хоunclassified
“…Согласно данным, полученным на изогенных линиях и коммерческих сортах, одни и те же чужеродные гены различаются по эффективности в разном генетическом окружении (Pretorius et al, 1990;Ren et al, 2012).…”
Section: влияние генотипической среды на проявление признаков устойчиunclassified
“…It has been reported that the short arm of chromosome 1B from common wheat (Triticum aestivum L.) is substituted by the short arm of chromosome 1R from rye (Secale cereale L.) in 'Salmon', thereby yielding 1BL/1RS translocation wheat. The transfer of the 1BL/1RS nucleus into the cytoplasm of different Aegilops species can result in male sterile wheat lines (Ren et al 2012;Zhou et al 2013). Thus, Zhang et al (1999) introduced the 1BL/1RS nucleus from wheat into the cytoplasm of different Aegilops species and successfully bred alloplasmic male sterile 1BL/1RS wheat lines with Ae.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered that the presence of rye secalins, as well as the reduced number of gluten loci causes the negative impact of translocation on the technological quality of wheat (Moonen and Zeven, 1984, Dhaliwal and MacRitchie, 1990, Martin and Carrillo, 1999. However, research results on the Ren et al (2012) report that the main reasons for inconsistent effect of 1BL/1RS translocation are different genetic bases of wheat varieties and different sources of rye chromosome. Also, they claim that the genetic diversity of 1BL/1RS lines is the result of not only different genetic basis of wheat and different sources of rye chromosome, but also of their interactions and of the translocation itself.…”
Section: Introductionmentioning
confidence: 99%